A Saturated Excess Runoff Pedotransfer Function for Vegetated Watersheds. Issue 4 (14th November 2013) - Steenhuis, Tammo S.; Hrnčíř, Miroslav; Poteau, Dina; Romero Luna, Eva J.; Tilahun, Seifu A.; Caballero, Luis A.; Guzman, Christian D.; Stoof, Cathelijne R.; Šanda, Martin; Yitaferu, Birru; Císlerová, Milena
Abstract : Since Hewlett and Hibbert's publication in 1967, there has been a slow recognition that saturated excess runoff is the main runoff mechanism in vegetated watersheds. Yet, most pedotransfer functions for predicting runoff are based on infiltration excess runoff. We, therefore, developed a simple pedotransfer function to predict saturation excess runoff, using data from eight watersheds on three continents. The runoff response was very similar for all watersheds, despite differences in climate, size, topography, and land use. Direct storm runoff occurred after a threshold amount of rainfall was exceeded. Runoff was linearly related to rainfall depth, indicating that a nearly constant proportion of the watershed was the source area. Size of source areas decreased with increasing depths of soils. The rainfall threshold was strongly dependent on the initial moisture conditions. The developed pedotransfer function for saturation excess runoff was used to predict water level fluctuation of two terminal lakes on the Caribbean Islands over a 25‐ to 30‐yr period with the rainfall threshold computed following Thornthwaite–Mather and baseflow from the remaining part of the watershed employing a linear reservoir model. Taking the simplicity of the prediction technique with only four calibrated parameters into account, lake levels were predicted reasonably well to very good, including the rise in the lake level in the last 10 yr when the climate in the region became wetter. It is expected that the linear relationship of rainfall and runoff holds for storms lasting several days and can simplify flood predictions.